Against the wall: Introduction to the Special Feature: Inscriptions of 'crisis': Street art, graffiti, and urban interventions. Issue 3 (4th July 2021) - Carastathis, Anna; Tsilimpounidi, Myrto
Abstract : In the imaginary of nation-states, and in much (forced) migration and border studies, the wall is the metaphor par excellence of 'hardened, securitised' and, ultimately, 'violent borders' (Jones 2016). It is not incidental that the previous US President's attempts to further institutionalise virulent anti-immigrant racism found purchase in the rallying cry 'Build a Wall.' While they function to restrict movement, walls, fences, and other border barriers are much more than a physical infrastructure separating the interior from the exterior of nationalised space. Although they appear to be a visual synecdoche for national sovereignty, Wendy Brown has argued that the frenzied construction of walls actually coincides with the 'waning' of national sovereignty in light of the penetration of neoliberal capitalist globalisation (2010, 23-24). In this introduction, we approach the 'instability' of walls (and state power) from another direction: we underscore the ways in which walls, in times of crisis, are repurposed as canvases of resistance, which communicate, amplify, and incite embodied resistance to authoritarianism and state violence. Not only walls built on borders—such as the wall at the Evros/Meriç border built by the Greek government—but walls inside nation-states proliferate, which form part of the hard fabric of our daily bordered reality.